Gambaran karakteristik pasien kondiloma akuminata dengan infeksi HIV/AIDS di RSUP Sanglah, Denpasar, Indonesia tahun 2011-2015 - Ida Bagus Gede Jayadharma; Anak Agung Gde Putra Wiraguna (Intisari Sains Medis, 2020)
Background: Condyloma acuminata, known as genital warts, is a sexually transmitted infection caused by a virus, namely Human Papilloma Virus (HPV). HPV infections are related to other sexually transmitted infections such as the Human Immunodeficiency Virus (HIV)/Acquired Immunodeficiency Syndrome (AIDS). This study aims to know the patient characteristics of condyloma acuminata in patients with HIV infection in Sanglah General Hospital, Denpasar, from January 2011 to December 2015.Methods: This research is a retrospective descriptive study with a cross sectional method. This research analyzed 58 patients of condyloma acuminata with HIV infection in Sanglah Public Hospital from January 2011 to December 2015. Research variables were based on age, sex, level of education, marital status, and work level. Data were analyzed using SPSS version 17 for Windows.Results: This study found that the prevalence of condyloma acuminata with HIV infection based on age was 15-24 years old (17.2%), 25-44 years old (81.0%), and 45-64 years old (1.7%). The results based on sex were 91.4% for males and 8.6% for females. The results based on education level were elementary school (8.6%), high school (53.4%), higher education (37.9%). The results based on work level were government employee (3.4%), private employee (77.6%), entrepreneur (10.3%), and do not have a job (8.6%). And the results based on marital status were married (13.8%) and single (86.2%).Conclusion: The highest prevalence of condyloma acuminata with HIV infection based on age was 25-44 years old, males gender, high school level of education, and working in the private sector. Latar Belakang: Kondiloma akuminata atau dikenal sebagai genital wart (kutil kelamin) adalah infeksi menular seksual yang disebabkan oleh virus, yaitu Human papilloma virus (HPV). Infeksi HPV kerap dikaitkan dengan infeksi menular seksual lainnya seperti Human Immunodeficiency Virus (HIV)/ Acquired Immunodeficiency Syndrome (AIDS). Tujuan penelitian ini untuk mengetahui karakteristik pasien kondiloma akuminata pada pasien yang terinfeksi HIV di Rumah Sakit Umum Pusat Sanglah Denpasar dari bulan Januari 2011 sampai dengan bulan Desember 2015.Metode: Penelitian ini merupakan penelitian deskriptif retrospektif, dengan metode cross sectional. Penelitian ini menganalisis 58 pasien dengan kondiloma akuminata dengan HIV di Poliklinik RSUP Sanglah pada periode Januari 2011 sampai dengan Desember 2015. Variable pada penelitian ini yaitu berdasarkan umur, jenis kelamin, tingkat pendidikan, status perkawinan, dan tingkat pekerjaan. Data dianalisis dengan SPSS versi 17 untuk Windows.Penelitian: Hasil dari penelitian ini didapatkan bahwa berdasarkan umur 15-24 tahun (17,2%), 25-44 tahun (81,0%), dan 45-64 tahun (1,7%). Berdasarkan jenis kelamin, yaitu laki-laki (91,4%) dan perempuan (8,6%). Hasil penelitian berdasarkan tingkat pendidikan, kelompok pendidikan dasar (8,6%), pendidikan menengah (53,4%), dan pendidikan tinggi (37,9%). Berdasarkan pekerjaan, yaitu kelompok PNS (3,4%), pegawai swasta (77,6%), wiraswasta (10,3%), dan kelompok tidak bekerja (8,6%). Dan berdasarkan status perkawinan didapatkan hasil yaitu kelompok menikah (13,8%) dan yang belum menikah (86,2%).Kesimpulan: Prevalensi kondiloma akuminata dengan HIV paling banyak berdasarkan kelompok umur yaitu kelompok usia 25-44 tahun, jenis kelamin laki-laki, kelompok pendidikan menengah, dan bekerja di sektor swasta.